2003
DOI: 10.2136/sssaj2003.0867
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Zone Tillage and Red Clover on Corn Performance and Soil Physical Quality

Abstract: benefits of conservation tillage with the yield benefits of conventional moldboard plow tillage (e.g., Pierce et Despite extensive research, reduced corn (Zea mays L.) performance is still encountered using conservation tillage on fine-textured al., 1992) for cool humid climatic zones. Here, a narrow soils in cool humid temperate climates. These problems are intensified zone 10 to 20 cm wide by 10 to 30 cm deep is conventionwhen corn is planted into residue from a previous crop such as winter ally tilled in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 9 publications
(14 reference statements)
1
35
1
Order By: Relevance
“…All these may be beneficial to the WUE improvement for croplands. Although many studies considered an increase in yield with adoption of no-till management (Beyaert et al, 2002;Grandy et al, 2006), no change or even a decrease in crop yield were also found in recent researches (Drury et al, 2003;Ogle et al, 2012;Powlson et al, 2014). Declines in yields are often attributed to cool and wet climatic conditions.…”
Section: Effects Of Management Practices On Wue and Neementioning
confidence: 99%
“…All these may be beneficial to the WUE improvement for croplands. Although many studies considered an increase in yield with adoption of no-till management (Beyaert et al, 2002;Grandy et al, 2006), no change or even a decrease in crop yield were also found in recent researches (Drury et al, 2003;Ogle et al, 2012;Powlson et al, 2014). Declines in yields are often attributed to cool and wet climatic conditions.…”
Section: Effects Of Management Practices On Wue and Neementioning
confidence: 99%
“…With ST, an improved the seedbed environment likely caused the greater plant populations. In poorly drained soils, strip-till can increased soil moisture evaporation, increased soil temperature (Bolton & Booster, 1981) and decreased soil bulk densities in the row compared with NT (Drury et al, 2003;Overstreet & Hoyt, 2008), which improves seedbed environment. This was particularly important early in the growing season.…”
Section: Phosphorus Placementmentioning
confidence: 99%
“…The practice consist of an implement tilling a narrow band, generally 15 to 20 cm wide and 15 to 20 cm deep, while leaving the rest of the soil undisturbed. In poorly drained soils, strip-till increased soil moisture evaporation, increased soil temperature (Bolton & Booster, 1981) and decreased soil bulk densities in the row compared with NT (Drury et al, 2003;Overstreet & Hoyt, 2008), which improves seedbed environment. Strip-till has been shown to increase corn yields compared to NT (Vetsch et al, 2007) and was equal to CT (Griffith et al, 1973;Randall et al, 2001).…”
mentioning
confidence: 99%
“…in the corn-soy-wheat rotation. The benefits of this practice have been well-documented [1][2][3][4][5][6][7][8]; however, they could be further enhanced if red clover was maintained as a living mulch between corn rows, rather than being terminated prior to corn (Zea Mays L.) planting.…”
Section: Introductionmentioning
confidence: 99%
“…Much research has been performed on the corn-soy-wheat rotation, on cover crops, and on strip-tillage independently. Researchers have noted the impact of red clover incorporation on corn productivity, several with specific focus on this rotation [1,2,[4][5][6][7][20][21][22]. Studies have examined the use of strip-tillage for corn [2,[17][18][19][20], and others have looked at the viability of integrating living mulch in corn [9,12,13,23].…”
Section: Introductionmentioning
confidence: 99%